Detection of Amyloid-β(1–42) Aggregation With a Nanostructured Electrochemical Sandwich Immunoassay Biosensor - Wang, Bing-Yu; Gu, Bien-Chen; Wang, Gou-Jen; Yang, Yuan-Han; Wu, Chia-Che (Frontiers in Bioengineering and Biotechnology, 2022)
Amyloid-β(1-42) (Aβ(1-42)) oligomer accumulations are associated with physiologic alterations in the brains of individuals with Alzheimer’s disease. In this study, we demonstrate that a nanostructured gold electrode with deposited gold nanoparticles (GNPs), induced via electrochemical impedance spectroscopy (EIS), may be used as an Aβ(1-42) conformation biosensor for the detection of Alzheimer’s disease. Monoclonal antibodies (12F4) were immobilized on self-assembled monolayers (SAMs) of the electrochemical sandwich immunoassay biosensor to capture Aβ(1-42) monomers and oligomers. Western blot and fluorescence microscopy analysis was performed to confirm the presence of Aβ(1-42) monomers and oligomers. EIS analysis with an equivalent circuit model was used to determine the concentrations of different Aβ(1-42) conformations in this study. We identified conformations of Aβ(1-42) monomers and soluble Aβ(1-42) oligomers using probe antibodies (12F4) by employing EIS. R_(Aβ(1-42)) indicates the sum resistance of impedance measured during Aβ(1-42) immobilization. 〖∆R〗_12F4 refers to the concentration of probe antibody (12F4) binding with Aβ(1-42). The concentrations of Aβ(1-42) oligomer was defined as the percentage of Aβ(1-42) aggregation 〖〖∆R〗_12F4/R〗_(Aβ(1-42)) . Experiment result shows that the biosensor can detect Aβ(1-42) oligomer accurately. The linear detection range for Aβ(1-42) oligomers was between 10 pg/ml and 100 ng/ml. The limit of detection was estimated to be 100fg/ml.